The use of infrared radiation in the treatment of skin laxity. (April 2014) - Felici, Marco; Gentile, Pietro; De Angelis, Barbara; Puccio, Livia; Puglisi, Aldo; Felici, Aldo; Delogu, Pamela; Cervelli, Valerio
Abstract Background: Cosmetic surgery and medicine are extremely interesting fields for a plastic surgeon. Lasers and lights determine ablation, contraction and regenerating stimulus in skin tissues. The aim of this study is to examine the use of infrared lights in treating facial and body skin laxity. Methods: Between 2007 and 2011, in the Department of Plastic and Reconstructive Surgery at the Hospital San Camillo-Forlanini, 303 patients were enrolled in the study and underwent laser therapy. The laser operates in wavelength from 1100 to 1800 nm. The treated areas are: face, neck, eyebrows, abdomen, legs and buttocks. Results: We have noticed no systemic complications. A case of a patient with a three days lasting erythema on both lower eyelids caused by laser therapy healed without any pharmacological therapy. Neither hyper- nor hypopigmentation of the skin was found. The satisfaction degree of patients has been: facial, neck and eyebrow lifting "very satisfactory" for 70% of the patients, "satisfactory" for 10%, "unsatisfactory" for 20%; for the other areas it was "very satisfactory" for 40%, "satisfactory" for 20% and "unsatisfactory" for 40%. Conclusion: The use of infrared radiation represents a valid alternative to surgical lifting, but cannot replace it. The infrared light technique used has turned out to be useful in contrasting skin laxity of the face and other parts of the body. The absence of scars and surgical risk makes this technique useable for a large number of patients.